AGRICULTURAL MACHINERY ACCIDENTS IN FEDERAL HIGHWAYS IN THE NORTHERN REGION OF BRAZIL - Macedo, Deivielison Ximenes Siqueira; Santos, Viviane Castro dos; Monteiro, Leonardo de Almeida; Dutra, Jefferson Auteliano Carvalho; Costa, Enio (ENERGIA NA AGRICULTURA, 2020)
AGRICULTURAL MACHINERY ACCIDENTS IN FEDERAL HIGHWAYS IN THE NORTHERN REGION OF BRAZIL DEIVIELISON XIMENES SIQUEIRA MACEDO¹, VIVIANE CASTRO DOS SANTOS², LEONARDO DE ALMEIDA MONTEIRO³, JEFFERSON AUTELIANO CARVALHO DUTRA4, ENIO COSTA5 1 Departamento de Engenharia Agrícola, Centro de Ciências Agrárias, Universidade Federal do Ceará -UFC, Departamento de Engenharia Agrícola, Bloco 804, Pici, 60020-181, Fortaleza-CE, Brasil. derilsiqueira@hotmail.com 2 Departamento de Engenharia Agrícola, Centro de Ciências Agrárias, Universidade Federal do Ceará -UFC, Departamento de Engenharia Agrícola, Bloco 804, Pici, 60020-181, Fortaleza-CE, Brasil. vihcs@live.com 3 Departamento de Engenharia Agrícola, Centro de Ciências Agrárias, Universidade Federal do Ceará -UFC, Departamento de Engenharia Agrícola, Bloco 804, Pici, 60020-181, Fortaleza-CE, Brasil. aiveca@ufc.br 4 Departamento de Engenharia Agrícola, Centro de Ciências Agrárias, Universidade Federal do Ceará -UFC, Departamento de Engenharia Agrícola, Bloco 804, Pici, 60020-181, Fortaleza-CE, Brasil. jeffersoncarvalho@hotmail.com 5 Departamento de Indústria, Instituto Federal de Educação, Ciência e Tecnologia do Ceará-IFCE, Av. Treze de Maio, 2081- Benfica, 60040-531, Fortaleza-CE, Brasil. prof.eniocosta@gmail.com ABSTRACT: The Brazilian North region is currently going through an agricultural expansion; however farm machinery misuse may increase accidents risks. In the present study was aimed to characterize accidents involving farm tractors on federal highways within the Northern region of Brazil by analyzing their indicators. The study was carried out between 2008 and 2011, in Department of Agricultural Engineering at the Federal University of Ceará, Fortaleza, Ceará state, Brazil in partnership with the Federal Highway Police – PRF. The parameters analysed were location (highway) where the accident happened, accident type and cause, information about victims age, time of day the incident happened and weather conditions. In order to find the minimum amount of samples, operational characteristics curves method was utilized. The collected data was submitted to a nonparametric statistics using frequency analysis and the chi-square test. Most accidents occurred due to lack of attention (62.79% of the total cases) and the main type of the accident was rear collision (32.00%). The afternoon period had more occurrences (38.67%) when compared to the other day periods. The BR-364 federal highway had the highest incidents amount on its extent (34.67%). The accident reports show 75.71% of the total cases happened in good weather conditions. Keywords: Causes of accidents; Security; Types of accidents. ACIDENTE COM MÁQUINAS AGRÍCOLAS EM RODOVIAS FEDERAIS DA REGIÃO NORTE DO BRASIL RESUMO: A região Norte brasileira vem passando por uma expansão agrícola, no entanto o uso demasiado de máquinas agrícolas pode aumentar o risco de acidentes. Assim, objetivou-se caracterizar os acidentes envolvendo tratores nas rodovias federais na região Norte do Brasil, analisando seus indicadores. O estudo foi realizado entre 2008 e 2011, no Departamento de Engenharia Agrícola da Universidade Federal do Ceará, Fortaleza, Ceará, em parceria com a Polícia Rodoviária Federal - PRF. Os parâmetros analisados ​​foram localização (rodovia) onde ocorreu o acidente, tipo de acidente, causa, informações sobre idade das vítimas, horário de ocorrência do evento e condições climáticas. Para encontrar a quantidade mínima de amostras, utilizou-se o método das curvas de características operacionais. Os dados coletados foram submetidos a estatísticas não-paramétricas utilizando-se análise de frequência e o teste do qui-quadrado. A maioria dos acidentes ocorreu por falta de atenção (62,79% do total de casos) e o principal tipo de acidente foi colisão traseira (32,00%). O período da tarde teve mais ocorrências (38,67%) quando comparado aos outros períodos do dia. A BR-364 teve a maior incidência em sua extensão (34,67%). Os relatórios de acidentes mostram 75,71% do total de casos ocorridos em condições climáticas boas. Palavras-Chave: Causa de acidente; Segurança; Tipo de acidente.